Eksistensi Tari Reog Kendang Tulungagung Sebagai Tradisi Kearifan Lokal - Dwi Luthfiana Nur Janah; Nur Alvi Puriamandawati; Fitania Syaharani Einadya Putri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Indonesia has a wealth of local traditions, one of which is the Reog Kendang Dance from Tulungagung. This dance was created in 1978 and shows the story of the journey of Kediri soldiers accompanying Ratu Kilisuci to Mount Kelud. The six dancers use large drums (dhodhog) to accompany the dance that depicts the procession. This article discusses the existence of the Tulungagung Reog Kendang Dance as a local wisdom tradition, as well as examining the history, values ​​contained, its development, and efforts to maintain this tradition. The approach to this research is qualitative research. Data collection in this research was carried out using observation, interviews and documentation methods at one of the studios in Gendingan village, Kedungwaru subdistrict, Tulungagung district. The results of this research include: 1) History of the Reog Kendang Tulungagung Dance, 2) The values ​​contained in each movement and artistic instrument of the Tulungagung Reog Kendang Dance, 3) The existence of the Tulungagung Reog Kendang Dance, 4) The development of the Tulungagung Reog Kendang Dance, 4) The development of the Tulungagung Reog Kendang Dance. and 5) Efforts to preserve the art of Reog Kendang Tulungagung Dance.